Electrical Synapses Enhance and Accelerate Interneuron Recruitment in Response to Coincident and Sequential Excitation - Alcami, Pepe (Frontiers in Cellular Neuroscience, 2018)
The properties of inhibitory circuits formed by interneurons are adjusted to efficiently inhibit principal cell activity. Despite interneurons being connected by electrical synapses throughout the brain, whether electrical synapses influence interneuron action potential generation in response to signals generated at chemical excitatory synapses remains elusive. The present article shows that electrical synapses regulate the rate, the probability and the delay of action potentials generated by electrically-coupled cerebellar basket cells when they are stimulated. Since the simultaneous excitation of two coupled cells decreases the voltage difference and thereby the current leakage across the gap junction between the two cells, I compared this situation with the case in which cells are stimulated separately in order to infer the contribution of the gap junction to their voltage response. In response to suprathreshold steady-state current injections, simultaneous depolarizations of coupled cells evoked an increase in firing rate and a shortening of action potential delay in both cells. Likewise, when both cells were stimulated with bursts of short-duration near-threshold currents their action potential probability strongly increased at 10 Hz, and to a lesser extent at 50 Hz. Moreover, spike probability was increased and spike delays were shortened in mice lacking the protein that forms gap junctions between basket cells, connexin36. Therefore, electrical synapses among basket cells decrease action potential probability and increase action potential delay, an effect that is reverted upon simultaneous excitation of coupled cells. Varying the delay of stimulation of coupled cells revealed that individual BC firing maximally facilitates when the cell is stimulated shortly (~5 ms) after a coupled cell is stimulated. These results suggest that owing to electrical synapses among them, coupled interneurons are efficient coincidence and sequence detectors which dynamically regulate the latency and the strength of inhibition onto postsynaptic targets depending on the degree of input synchrony in the coupled interneuron network.